Sitting pressure during wheelchair propulsion and handcycling: effects of backrest angle, movement intensity and cushion type. - Snoek, Thom; Haarler, Annelaura; van Orsouw, Ludwine; Janssen, Thomas W. J.; de Groot, Sonja; Kouwijzer, Ingrid (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: The main aim of this study was to compare sitting pressure (peak pressure index (PPI) and peak pressure gradient (PPG)) between a daily wheelchair and fixed-frame handcycle, thereby assessing the effect of handcycle backrest angle, movement intensity and cushion type. Materials and methods: Twenty able-bodied participants performed static and dynamic (two intensities) tests in a wheelchair and handcycle. A honeycomb wheelchair cushion and standard foam handcycle cushion were used. Handcycle backrest angles were 45° and 60°. The PPI and PPG at the sacro-coccygeal (SC) and ischial tuberosity (IT) regions were determined with a pressure mat. Results: PPI at the IT-region was higher in the 60° handcycle condition than in the wheelchair (p = 0.04), while PPG at the IT-region did not differ significantly between the wheelchair and handcycle conditions (p > 0.05). PPI and PPG were higher at the 45° handcycle SC-region compared to the wheelchair IT-region (p < 0.03). PPI and PPG at the IT-region were higher with the 60° than with the 45° backrest angle (p < 0.01), while at the SC-region PPI was higher with the 45° backrest angle (p = 0.047). No clear influence of movement intensity was found. PPI and PPG at the IT-region and PPI of the SC-region in the handcycle were significantly lower with the wheelchair cushion than with the handcycle cushion (p < 0.01). Conclusion: Overall, sitting pressure was higher in the handcycle compared to the daily wheelchair. For handcyclists using an upright position, it is recommended to use a cushion designed to redistribute pressure, thereby reducing internal tissue pressure and shear. IMPLICATIONS FOR REHABILITATION: Individuals with a spinal cord injury are at high risk of developing pressure ulcers at the ischial tuberosities (ITs) and the sacro-coccygeal (SC) region due to elevated sitting pressure. The sitting pressure at the IT-region is higher during handcycling in an upright position compared to wheelchair propulsion, while the sitting pressure at the SC-region is higher during handcycling in a less upright position. The use of a honeycomb wheelchair cushion reduces the sitting pressure in the handcycle compared to a standard foam handcycle cushion. For handcyclists, it is recommended to use a cushion designed to redistribute pressure, thereby reducing internal tissue pressure and shear.